(untitled) (Modern American Journal of Engineering, Technology, and Innovation, 2026)
Artificial intelligence scanners are advanced technology capable of fundamentally changing the processes of converting, storing, and managing library resources in electronic form. This article analyzes the directions of using artificial intelligence scanners in libraries, their main advantages, capabilities, and prospects for implementing artificial intelligence in library activities.